Students’ Attitudes and Behavioral Intentions in Using Moodle for German Language Learning: A TAM-Based Study - Astrid Dyah Retno Saputri; Pepen Permana; Irma Permatawati (South Sulawesi Education Development (SSED), 2025)
This study aims to examine how how students in the German Language Education Program at Universitas Pendidikan Indonesia perceive and intend to use Moodle as a learning platform. A quantitative approach was employed, utilizing a survey based on the Technology Acceptance Model (TAM) to assess students' attitudes and behavioral intentions toward Moodle. The questionnaire assessed students' attitudes and behavioral intentions using a 4-point Likert scale, and the data were analyzed using Spearman's rho correlation. The findings revealed that students showed a generally positive attitude towards Moodle, with an average score of 3.62, indicating their recognition of the platform’s utility and its potential to engage them in the learning process. Moodle features such as discussion forums, quizzes, and multimedia materials were identified as key contributors to enhancing the learning experience. Moreover, students demonstrated strong behavioral intentions to continue using Moodle, with an average score of 3.57. Spearman’s rho analysis revealed a significant positive correlation between students’ attitudes and their behavioral intentions (r = 0.679). These findings support the TAM assumption that individuals' attitudes significantly influence their willingness to adopt technology. While this study is limited to the German Language Education Program, the results offer valuable insights for optimizing technology-based learning platforms. Further qualitative research is suggested to gain deeper insights into students’ learning experiences with Moodle.